2019
DOI: 10.1371/journal.pone.0210223
|View full text |Cite
|
Sign up to set email alerts
|

Rab5-independent activation and function of yeast Rab7-like protein, Ypt7p, in the AP-3 pathway

Abstract: The small GTPases, Rab5 and Rab7, are key regulators at multiple stages of the endocytic/endolysosomal pathway, including fusion and maturation of endosomes. In yeast, Vps21p (Rab5 homolog) recruits a GEF for Rab7 and activates the downstream Ypt7p (Rab7 homolog) on endosomal membrane. Although the model of this sequential activation from Vps21p to Ypt7p in the endocytic pathway has been established, activation mechanism of Ypt7p in the Vps21p-independent pathway has not been completely clarified. Here we show… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 47 publications
1
6
0
Order By: Relevance
“…The quantitative analysis of the distribution and extent of clustering of the antibodies against the intracellular proteins Rab5, Rab7, and LAMP-1 reveal that they are highly clustered (on the order of 500-1000 antibodies per cluster), that these clusters are large (0.2-0.6 μm), and that they are distributed evenly intracellularly. These observations are consistent with each of these proteins being associated with organelles such as the endosomes and the lysosomes [51,52,53].…”
Section: Discussionsupporting
confidence: 83%
“…The quantitative analysis of the distribution and extent of clustering of the antibodies against the intracellular proteins Rab5, Rab7, and LAMP-1 reveal that they are highly clustered (on the order of 500-1000 antibodies per cluster), that these clusters are large (0.2-0.6 μm), and that they are distributed evenly intracellularly. These observations are consistent with each of these proteins being associated with organelles such as the endosomes and the lysosomes [51,52,53].…”
Section: Discussionsupporting
confidence: 83%
“…There have been earlier circumstantial indications of the existence of a Rab5-independent pathway specifically in the context of viral infections, as well as trafficking to yeast vacuole (Shimamura et al, 2019;Toshima et al, 2014). It has been shown that some viruses use unconventional endocytosis, such as Herpes Simplex Virus 1 (Tebaldi et al, 2020), SARS-CoV (Castan ˜o-Rodriguez et al, 2018), Lassa virus, the Amr53b and We54 strains of LCMV (lymphocytic choriomeningitis virus) (Kunz, 2009;Pasqual et al, 2011;Quirin et al, 2008;Rojek et al, 2008), Lujo virus (Kunz and de la Torre, 2017;Raaben et al, 2017) and some influenza A strains (Wu et al, 2018) that appear to skip the early Rab5-positive endosomes.…”
Section: Discussionmentioning
confidence: 99%
“…There have been earlier circumstantial indications of the existence of a Rab5independent pathway specifically in the context of viral infections, as well as trafficking to yeast vacuole 122,123 . It has been shown that some viruses use unconventional endocytosis, such as Herpes Simplex Virus 1 124 , SARS 125 , Lassa virus, the Amr53b and We54 strains of LCMV (lymphocytic choriomeningitis virus) [126][127][128][129] , Lujo virus 130,131 and some influenza A strains 132 that appear to skip the early Rab5-positive endosomes.…”
Section: Discussionmentioning
confidence: 99%